Embracing our time : The Sacrament of interfaith friendship - Cooper, Lynn A. (USA Fortress Press, 2025)
"Embracing Our Time provides practical resources for interfaith engagement rooted in a Catholic perspective. Drawing on trinitarian, sacramental, and feminist theologies, Cooper shows that interreligious collaboration is a concrete expression of the interdependence at the heart of Catholic faith"--
Keywords: Friendship; Christian Union